(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Job stress directly effects the employee’s job performance. If the employees are feeling stress on their job and are yet satisfied with their job then this is positive impact. If employees feel stress on their job and are not satisfied with their job then this is negative impact. Some pressures are helpful for the organization and some pressures and energy is necessary to change the social flexibility. This study focuses on studying the stress and its impact of job performance of employees in medical field including Doctors, Nurses and Accountants. It also analyse the symptoms of stress and causes of stress. It analyses the coping strategies to reduce the stress of the employees. By the application of x² test, There is no significant relationship between the demographic profile of the respondents and their level of symptoms of stress. By the Application of ’F’ test "there is no significant relationship between demographic profile of the respondents and their level of using coping strategies to reduce stress". More importance to recreational activities by conducting outing and mind refreshing sessions, organizing workshops and discussions are essential to enable the employees to get more acquaintance related to their nature of job. Relaxation techniques like Yoga and meditation should be arranged by the organization. New Training programmes should be conducted for employees.